ENGLISH FOR SPECIFIC PURPOSES IN THE CONTEXT OF MILITARY REFORM: TERTIARY LEVEL - Strilets, L. К.; Kumpan, S. М. (Honor and Law, 2019)
The article deals with challenges of ESP training in the National Academy of the National Guard of Ukraine and the ways to meet them within the reform of higher military education in Ukraine; current situation is analyzed, the problem areas are determined and the prospects are outlined.